PEMBUATAN TRAINING KIT SISTEM PENERANGAN TOYOTA KIJANG 5K Disusun Oleh: ANDHIKA ANDJARWADI 10/298498/NT/13952 PROGRAM DIPLOMA TEKNIK MESIN SEKOLAH VOKASI UNIVERSITAS GADJAH MADA YOGYAKARTA 2013 - , ANDHIKA ANDJARWADI, Ir. Greg Sukartono ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Automotive is applied physics and dynamics of the mechanics of motion. But automotive was not only just mechanics and motion dynamics course, other disciplines also took part in the development of the automotive world. Other branches of science such as, chemical, production processes, materials science, structural mechanics, heat transfer, thermodynamics and electronics. Electronics is a branch of Automotive supporters. For example, the gasoline engine may not work without electrical spark from the spark plug. Means of lighting also strongly supports the mobility of a vehicle for their activities during the day and night. On the basis of education and training for academic, to facilitate the mastery generally electrical systems and lighting system particulary this final project implemented. The aim of making Training Kit Toyota 5K Lighting System as a means of education and training in the control of electrical systems generally and information systems particulary, to simplify the visual side. Final project that writters make, certain three main topics namely electronic components, wiring diagrams, and process training kit. In the electronics field, this final project talked more about the workings of a number of components such elektonics lights, flasher, relays and electromagnetic waves in current-carrying wires. Other scope in this final project is the wiring diagram. procces Training Kit is divided into 3 main processes, namely welding frame, panel board formation, and installation / assemble the cables. From the test results, all sub-systems and all the circuit works fine and as expected.